Establishing Character of Educational Tourism in Kampung Literasi Sidoarjo Through Playground Design - Fairuz Mutia; Diana Aqidatun Nisa; Azkia Avenzoar; Dominikus Aditya Fitriyanto (Future Science, 2021)
Tourist destinations, particularly in a village, need to attract attention to become magnetite for domestic and foreign tourists. Tebel Village then imaged it as an education and literacy village to authenticate its role as a tourist village. At some points, the village has made reading spots and educational areas. Perversely, due to funding and human resources constraints, not all areas are well designed. The playground area located in front of the river is not well planned. The existing murals are not sustainable and tend to be poorly maintained. One of the attempts to enhance the quality and character of this tourist environment is through a comprehensive design, both from architecture and visual communication design. This community assistance is a design applied to the playground area and gets a good response from society. This project is designated to reinforce the identity of the tourist village in Kampung Bendo, Tebel, as a village that prioritizes elements of literacy and education as a tourist spectacle.